Ovariectomy in dogs: comparison between medial and lateral approach - Masache, Juan L. (2016)
The aim of this study was to evaluate the ovariectomy technique by lateral or medial approach as a sterilization method in bitches. The variables were surgical time, quantification of bleeding during surgery and degree of pain assessed at 2, 4, 6, 18 and 24 hours after surgery, following the short form of the Glasgow composite pain scale. A total of 70 apparently healthy females were selected and randomly distributed in two groups. Group 1 was sterilized by lateral approach ovariectomy (paracostal) and Group 2 by medial approach ovariectomy (celiotomy). In the statistical analysis, the additive effects in the model were: approach technique and weight, age, breed and parity of the animal. Estimates of the differences between surgical methods were obtained by generalized least square. Data recording of the surgical procedure and observations after surgery were carried out by the same person. The results showed statistical differences for the approach technique and animal weight and age. For the variable surgical time, the lateral approach ovariectomy was significantly quicker. None statistical differences between techniques were found due to quantification of bleeding and degree of pain. These results indicated that ovariectomy by lateral approach is a procedure that requires less surgical time.